Analisis Pengaruh Kualitas Pelayanan pada PDAM Tirtanadi di Kota Medan - Haliza, Haliza (Masyarakat Ekonomi Syariah Bogor, 2024)
Service quality is a top priority for PDAM Tirtandi customers in Medan City. The purpose of this research is to analyze the quality of drinking water services offered to PDAM Tirtandi customers in Medan City, as well as the supporting and inhibiting factors. The theory used is from Zeithml and Bitner, which is a measure of quality resulting from several indicators of reliability, responsibility, security, empathy and concrete evidence. The research method used is a qualitative approach through observation, interviews and documentation. The results of this study indicate that the quality of drinking water supply in PDAM Tirtanadi Medan City is not fully effective. This can be said to be ineffective based on several metrics that are used as benchmarks for research that is not carried out optimally. Supporting and inhibiting factors also determine the quality of services offered. Keywords: Quality, Service, PDAM